Osteoporosis in Rett Syndrome: A Study on Normal Values - Lilit Zysman; Meir Lotan; Bruria Ben-Zeev (The Scientific World Journal)
Osteoporosis is the reduction of calcium density in bones, usually evident in postmenopausal females, yet the tendency for osteoporosis can also be identified at a young age, especially in patients with chronic diseases, disabilities, and on chronic anticonvalsant treatment. Individuals with Rett syndrome (RS) have been found to show signs of osteoporosis at a young age. This condition may cause pathological fractures, inflict pain, and seriously damage mobility. In such cases, the quality of life of the individual and her primary caretakers will be severely hampered. This article reviews the current knowledge of the phenomenon and suggests some clinical directions for the individual with RS who shows signs of osteoporosis. The article also presents novel findings from a screening test of bone strength in 35 individuals with RS at different ages using the Sunlight Omnisense 7000P ultrasound apparatus. The primary results from this investigation showed a strong and significant positive correlation between calcium intake and bone strength (p < 0.0001) as well as bone density Z values (p < 0.005). The occurrence and frequency of fractures were found connected with reduced bone strength in measurements of both the radius (p < 0.0001) and the tibia (p < 0.004) as well as with negative bone strength Z values (p = 0.03). Other findings specified within the content of the article support the implementation of a comprehensive antiosteoporotic preventive management for this population.